Endocrine responses to snouted cobra (Naja annulifera) and African puffadder (Bitis arietans) envenomation in dogs - Schoeman, Johan P. (University of Pretoria, 2025)
Dissertation (MSc (Companion Animal Clinical Sciences))--University of Pretoria, 2025.